The features of the nitric oxide system in the left ventricle myocardium in the rats with experimental intermittent hypoxia of different duration - Yu. M. Kolesnyk; M. I. Isachenko; O. V. Melnikova (Patologìâ)
The aim was to determine the features of the NO system status in the left ventricular myocardium in the rats with intermittent hypoxic hypobaric hypoxia during 15 and 60 days.